1250: The Regional Ruler al-Azraq Writes to the Queen of Aragón (Transmediterranean History, 2021)
This article examines a letter from the Muslim regional ruler and rebel leader al-Azraq to the Queen of Aragón. The letter was written in the context of the first major uprising of Muslims in the Kingdom of València (1247–1258). Based on an analysis of the document's content, the article analyses the diplomatic etiquette that characterised the relations between the crown and the rebels. Moreover, it inserts al-Azraq's rebellion into the supra-regional context of the so-called "Reconquista," which reached a critical point around the middle of the thirteenth century.
Keywords: diplomacy; letter; Muḥammad b. Huḏayl al-Azraq; Reconquista; Crown of Aragón; James I of Aragón; rebellion; Muslims under Christian rule; negotiations